The importance of dignity among higher-education faculty members who support student mental health - Erica B. Riba (Academia Mental Health & Well-Being)
In the past two decades, mental health among students at colleges and universities in the United States has been a widely studied topic. Fortunately, there has been some improvement in anxiety and depression among college students in recent years. This improvement may be due to greater attention to and investment in mental health promotion and resources, less stigma surrounding mental health awareness, and changes in campus culture related to the COVID-19 pandemic. This progress may also be related to an increase in training, resources, and support that faculty members received from their institutions. Adding to the literature, studies have found that faculty members in higher education have a key role in supporting college students’ mental health, but they are not often directly asked about how they see themselves in this role. This brief paper focuses on the current literature, aiming to more closely define the role of faculty members in supporting student mental health, offering examples and faculty stories of how dignity may be demonstrated and better understood. Key themes from both the brief literature review and highlights from these conversations include the importance of faculty members demonstrating compassion toward students, empathizing with the struggles and hardships of their students, and the need for higher-education institutions to elevate the values of dignity and respect towards faculty members.